Epigenetic Regulation of Kaposi’s Sarcoma-Associated Herpesvirus Latency - Campbell, Mel; Yang, Wan-Shan; Yeh, Wayne W.; Kao, Chen-Hsuan; Chang, Pei-Ching (Frontiers in Microbiology, 2020)
Kaposi's sarcoma-associated herpesvirus (KSHV) is an oncogenic -herpesvirus that infects humans and exhibits a biphasic life cycle consisting of latent and lytic phases. Following entry into host cells the KSHV genome undergoes circularization and chromatinization into an extrachromosomal episome ultimately leading to the establishment of latency. Interestingly, the KSHV episome is organized into distinct chromatin domains marked by variations in repressive or activating epigenetic modifications, including DNA methylation, histone methylation, and histone acetylation. Thus, the development of KSHV latency is believed to be governed by epigenetic regulation. In the past decade, interrogation of the KSHV epitome by genome-wide approaches revealed a complex epigenetic mark landscape across KSHV genome and showed the important regulatory role of epigenetic modification in modulating the development of KSHV latency. Here, we highlight many of the findings regarding the role of DNA methylation, histone modification, post-translational modification (PTM) of chromatin remodeling proteins and the contribution of long non-coding RNAs (lncRNAs) in regulating KSHV latency development.